2022
DOI: 10.1111/jocd.14757
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of hyaluronic acid fillers for lip augmentation in a Chinese population

Abstract: Full lips are considered youthful and attractive. Lip augmentation is one of the most popular cosmetic procedures performed today, especially in Caucasian populations. 1 Previous studies suggested that hyaluronic acid (HA) is an acceptable material for nonsurgical facial rejuvenation. 2 As living standards are improving, Chinese have paid increasing attention on to the facial rejuvenation. A recent consumer survey revealed that there is a gradual increase in Chinese consumer demand for lip augmentation. Regret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Results showed that HA was well tolerated by patients and safe, with few reported long-term side effects. 5 Other results showed that different hyaluronic acid-based products were effective and safe in improving lip volume and appearance, with an average duration of about nine months. 6 The application is usually well tolerated by patients, with few reported side effects, such as pain, swelling, and bruising at the injection site.…”
Section: Brands and Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that HA was well tolerated by patients and safe, with few reported long-term side effects. 5 Other results showed that different hyaluronic acid-based products were effective and safe in improving lip volume and appearance, with an average duration of about nine months. 6 The application is usually well tolerated by patients, with few reported side effects, such as pain, swelling, and bruising at the injection site.…”
Section: Brands and Variantsmentioning
confidence: 99%
“…The results showed that hyaluronic acid enhances lip volume and reduces perioral wrinkles, with a favorable safety profile. 4 In addition, a retrospective chart review study by Guo et al, 5 evaluated the long-term safety of HA for lip fillers in a large sample of patients. Results showed that HA was well tolerated by patients and safe, with few reported long-term side effects.…”
Section: Brands and Variantsmentioning
confidence: 99%